ANALISIS STRUKTUR BALOK RANGKA TERSUSUN BAJA H-BEAM TERHADAP BEBAN KOLAM RENANG PADA PROYEK EAST COAST CENTER II PHASE 2 PAKUWON CITY SURABAYA - Rida Pribady; Sumaidi Sumaidi; Wahyu Kartini (Racic : Rab Construction Research, 2025)
The existence of a swimming pool above the building plus the size of the swimming pool makes the designed structure must be safe for its users. One of the structural methods used is a combination of structures where the use of a steel frame beam structure is connected to a concrete column. The steel frame beam structure uses two H-beam steel profiles arranged in a Bailey frame model. The frame beam uses a HWF 350.350.12.19 arranged profile with stiffening using a 20 mm thick coupling plate. In this structure, all connections use the welding connection method. The use of a steel frame beam structure is expected to be able to support the load of a swimming pool that stretches 27 m x 20.5 m. To determine the behavior and response of the steel frame beam structure to the load, a stability analysis of the steel frame beam structure was carried out using an auxiliary program. From the results of the analysis of the compressive and tensile control of the axial force of the frame beam, it is able to support the swimming pool load with the largest compressive control value of bar B11 11994701.59 N > 8375985.50 N and the largest tensile control of bar B19 16317000 N > 10384957.50 N.